Local Nanostructured Ashes Synthesized by Incineration, Pulverization and Spectrophotometric Characterization of Solid Wastes Ashes for Use as Admixtures in Soil Stabilization - Onyelowe, Kennedy Chibuzor (International Journal of Sustainable Construction Engineering and Technology, 2016)
Nanostructured ash materials were locally synthesized by the spectrophotometric characterization method and applied in the stabilization of lateritic soils to evaluate the effect of the ashes on the strength properties of the lateritic soil. The ashes are products of the incineration and complete pulverization of some selected biodegerable solid waste materials. Results showed that the ashes were nanomaterials by size, reactive surface, absorbance and texture. And the studied soil was found to be an A-2-7 soil, according to AASHTO classification method. These ash materials were mixed with the soil in varying proportions of 3%, 6%, 9%, 12% and 15% by weight of dry soil and their respective effects on the soil evaluated. The California bearing ratio and unconfined compressive strength results improved remarkably. The results showed that the ash materials are good admixtures in the stabilization of lateritic soils in pavement sub-grade and sub-base construction and other civil engineering works. These materials are secured free of cost and by implication reduced the cost of stabilizing the lateritic soils hence a cost effective stabilization was achieved.